Vertigo Due to Posterior Circulation Stroke - Kim, Ji Soo; Lee, Hyung (Seminars in Neurology, 2013)
Stroke in the distribution of the posterior circulation may present as acute onset spontaneous vertigo and imbalance. Although vertigo due to posterior circulation stroke is usually associated with other neurologic symptoms or signs, small infarcts in the cerebellum or brainstem can present with vertigo without other localizing symptoms. Approximately 17% of patients with isolated posterior inferior cerebellar artery territory infarction presented with isolated vertigo, nystagmus, and postural unsteadiness. A head impulse test can differentiate acute isolated vertigo associated with cerebellar stroke from more benign disorders involving the inner ear. Sometimes acute isolated audiovestibular loss can be the initial symptom of impending posterior circulation ischemic stroke (particularly within the territory of the anterior inferior cerebellar artery). In this case, evaluation of isolated audiovestibular loss may prevent the progression of acute vertigo and hearing loss into more widespread areas of infarction in the posterior circulation. In this article, the clinical syndromes and signs of acute vestibular syndrome due to posterior circulation stroke involving the brainstem and cerebellum are summarized.
Keywords: vertigo; stroke; posterior circulation; brainstem; cerebellum